SISTEM PENJADWALAN MATA KULIAH, PRAKTIKUM, DAN KULIAH PENGGANTI DENGAN METODE ITERATIVE FORWARD SEARCH - Nadia Yanitra; Lely Hiryanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Class, laboratory, and substitute class application is made by using Iterative Forward Search. This application will deliver optimized schedule of class, laboratory, and substitute class scheduling. The sample case is Faculty of Information Technology at Tarumanagara University. Iterative Forward Search is used to deliver schedule of class, laboratory, and substitute class with consideration of part time lecturer’s time availability, no violation of hard constraint, and as few as possible violation of soft constraint. The results still indicate the violation of soft constraint and the mismatch schedule to part time lecturer’s time availability. The most frequent violation of soft constraint is when two classes; one class is in year x and the other one is in year (x-2) or year (x+2); were scheduled in the same timeslot. The mismatch schedule to part time lecturer’s time availability is caused by violation of hard constraint in the pointed timeslot. Key wordsIterative Forward Search, Fakultas Teknologi Informasi Universitas Tarumanagara, University Course Timetabling Problem